Fast and robust image watermarking method in the spatial domain - Zihan Yuan; Qingtang Su; Decheng Liu; Xueting Zhang; Tao Yao (IET Image Processing, 2020)
To solve the copyright protection problem of a colour image, a new blind colour image watermarking method combining a discrete cosine transform (DCT) in the spatial domain is presented in this study. The advantages of the spatial‐domain watermarking algorithm and frequency‐domain one are made full use in this scheme. Based on the different quantisation steps in red, green, and blue three‐layer images, the processes of watermark embedding and blind extraction are completed in the spatial domain without a real DCT domain. The scheme is realised by using the unique features of the direct current (DC) coefficient and the relativity of DC coefficients between adjacent pixel blocks. This scheme can effectively solve the problems of the large‐capacity colour image watermarking algorithm, such as long‐running time and weak robustness. Comparing with other advanced watermarking algorithms, the presented scheme has better invisibility, stronger robustness, and higher real‐time performance.